EFFECT OF INCOME PARENTS, FAMILY ENVIRONMENT AND MOTIVATION LEARNING ON STUDENT ACHIEVEMENT SUBJECT OF SOCIAL SCIENCE IN ELEMENTARY SCHOOL 2 KUTOANYAR SUB-DISTRICT TULUNGAGUNG DISTRICT TULUNGAGUNG YEARS LESSONS 2015-2016 - septiana dwi puspitosari; imam sujono; imam sukwatus sujai (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2016)
This study basically want to know whether there is the influence of parents 'income level, family environment and students' motivation on student achievement social science subjects in Elementary School 2 Kutoanyar Tulungagung 2015-2016 school year, which is divided into four hypotheses. Total sample of 60 students Elementary School 2 Kutoanyar Tulungagung 2015-2016 school year. Analysis of the data used is quantitative analysis with SPSS for Windows. Some stages of the analysis carried out are (1) Frequency Analysis, (2) testing requirements analysis, consists of normality test, linearity, multicollinearity test, and (3) test the hypothesis that consists of simultaneous test and partial test. Based on the test results conducted simultaneous states there is a significant relationship jointly between parental income level, family environment and motivation to learn together on student achievement social science subjects in Elementary School 2 Kutoanyar Tulungagung acceptable. The calculation result F count equal to 69.669 while the Ftable at 4.00 (Î± = 0.05 df 1). This shows that Fcount (69.669) F table (4.00). Ha research hypothesis can be accepted as true. From the results of the partial test calculations have been done, tcount of 24.409 compared to ttabel (db = 60) is 1.671 to É‘ = 0.05, so tcount ttable then Ha Ho accepted and rejected. In other words, reject Ho and accept Ha for the whole hypothesis testing. Based on the above conclusion, the teacher should always follow the development of various methods of learning so as to convey the material to the students is not monotonous and more ready to accept innovation and the development of education, and students are motivated to increase interest in learning materials science social as one way to prepare to become an independent person and able to think critically for the progress of the Indonesian nation.